2018
DOI: 10.3389/fimmu.2018.00338
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Manifestations of the Activated Phosphoinositide 3-Kinase Delta Syndrome

Abstract: The activated phosphoinositide 3-kinase δ syndrome (APDS), also known as p110δ-activating mutation causing senescent T cells, lymphadenopathy, and immunodeficiency (PASLI), is a combined immunodeficiency syndrome caused by gain-of-function mutations in the phosphoinositide 3-kinase (PI3K) genes PIK3CD (encoding p110δ: APDS1 or PASLI-CD) and PIK3R1 (encoding p85α: APDS2 or PASLI-R1). While the disease is clinically heterogeneous, respiratory symptoms and complications are near universal and often severe. Infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…We postulate that the transitional B cells which are expanded in APDS patients may not just be precursors to more mature B cells, but also include cells that are functionally equivalent to the CD19 + B220 − cells that we have identified in p110δ E1020K mice and thus may also contribute to the increased susceptibility to S. pneumoniae infection and hence to the high incidence of bronchiectasis characteristic of this disease 15 . In this context, it is interesting that CD19 + B220 − B cells had previously been described as immature progenitors in the bone marrow 37 , rather than a functional PI3Kδ dependent subset found in peripheral tissues as we describe here.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We postulate that the transitional B cells which are expanded in APDS patients may not just be precursors to more mature B cells, but also include cells that are functionally equivalent to the CD19 + B220 − cells that we have identified in p110δ E1020K mice and thus may also contribute to the increased susceptibility to S. pneumoniae infection and hence to the high incidence of bronchiectasis characteristic of this disease 15 . In this context, it is interesting that CD19 + B220 − B cells had previously been described as immature progenitors in the bone marrow 37 , rather than a functional PI3Kδ dependent subset found in peripheral tissues as we describe here.…”
Section: Discussionmentioning
confidence: 82%
“…One of the defining characteristics of APDS patients is an increased proportion of CD24 + CD38 + B cells defined as transitional B cells 1012, 14, 15 . Intriguingly, production of IL-10 is a characteristic of these B cells as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 In addition, the patients with earlyonset CVID are more likely to have a monogenetic defect (such as, LRBA, CTLA-4, PIK3CD) that may lead to bronchiectasis to due severe immune dysregulations that are associated with an inflammatory response in the lung. [23][24][25][26] This may be different from the development of bronchiectasis in patients with adult-onset CVID, in which the etiology may be more chronic and patients may less often have inflammatory lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that patients with CVID and parental consanguinity that diagnosed in childhood are more severely affected by autoimmunity, inflammatory lung disease, and enteropathy than adults diagnosed later in life . In addition, the patients with early‐onset CVID are more likely to have a monogenetic defect (such as, LRBA, CTLA‐4, PIK3CD) that may lead to bronchiectasis to due severe immune dysregulations that are associated with an inflammatory response in the lung . This may be different from the development of bronchiectasis in patients with adult‐onset CVID, in which the etiology may be more chronic and patients may less often have inflammatory lung disease.…”
Section: Discussionmentioning
confidence: 99%